GT Eco-Social: Uma Experiência de Ensino- Pesquisa-Extensão - Barcellos, Fernando H.G.; Tavares, Ana Claudia D.; Moreira, Erika Macedo; Seva, Janaina Tude; Moreira, Juliana G.; Costa, Rodolfo B. M. Lobato da (Interagir pensando a extensão, 2016)
GT Eco-Social: Uma Experiência de Ensino-Pesquisa-Extensão